Regional topographic classification in the North Shaanxi Loess Plateau based on catchment boundary profiles. (June 2017) - Li, Min; Yang, Xin; Na, Jiaming; Liu, Kai; Jia, Yini; Xiong, Liyang
Topographic classification and mapping are fundamental topics in geomorphology and have many promising applications. This study aimed to achieve landform classification using the catchment boundary profile (CBP) in the area of the North Shaanxi Province. CBPs were extracted, and seven indices were proposed and calculated to describe the profile features. Spatial maps of these indices were generated by interpolating 81 sample areas in the North Shaanxi Province of China. Finally, a topographic regional map was generated through multi-resolution segmentation after integrating the spatial maps of the seven indices. Results showed that the CBP indices were typical and representative to describe the terrain characteristics in the North Shaanxi Province and revealed their diverse spatial patterns. The investigated area was classified into 14 topographic units. The requirements of maximizing internal homogeneity while minimizing external homogeneity in terms of morphological characteristics were satisfied through the analysis of the terrain texture, topographic features, and land surface parameters. A comparison with the reference map showed that the regional classification differed from the geomorphologic map, given the different classification systems. However, the regional classification provided new knowledge of topographic features and spatial patterns in the macro scale. A comparison with other classification method indicated the advantage of the CBP-based method, which could distinguish the landforms of loess tableland, loess ridge, and loess hill that are the typical characteristics of loess landforms. The sensitivity analysis revealed that the differences in CBP indices, except for roughness and fractal dimension (FD) from different landforms, would increase with the digital elevation model (DEM) resolution becoming coarser, which indicates that the CBP-based method could be applied on a coarser resolution DEM if the differences of roughness and FD from different landforms could be identified at this coarse DEM level.